2019
DOI: 10.1111/ijcp.13438
|View full text |Cite
|
Sign up to set email alerts
|

Age, height, BMI and FBG predict prostate volume in ageing benign prostatic hyperplasia: Evidence from 5285 patients

Abstract: Aims Several studies have reported a potential association between prostate volume (PV) and prostate disease. Here, we classified the risk factors for PV among benign prostatic hyperplasia (BPH) patients. Methods In all, 4293 BPH patients with available clinical information were enrolled. Body mass index (BMI) was obtained as weight divided by height squared. PV was calculated as length × width × height (cm) × π/6. Mann‐Whitney U tests were used to determine the differences between PV subgroups. Univariate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
4
1
Order By: Relevance
“…A study of a predictive model for the risk of BPH in 5284 elderly men in central China showed that BMI was an independent risk factor. 33 Interestingly, this study also showed that prostatic calcification was positively associated with BPH, 33 which is different from the result in the present study. BMI mainly responds to generalized overweight and obesity 34 and does not describe a good distinction between muscle and fat content.…”
Section: Discussioncontrasting
confidence: 99%
“…A study of a predictive model for the risk of BPH in 5284 elderly men in central China showed that BMI was an independent risk factor. 33 Interestingly, this study also showed that prostatic calcification was positively associated with BPH, 33 which is different from the result in the present study. BMI mainly responds to generalized overweight and obesity 34 and does not describe a good distinction between muscle and fat content.…”
Section: Discussioncontrasting
confidence: 99%
“…And BMI was an important confounding factor in the PV-IBIL relationship (Tables 3-5). This finding is consistent with previous reports, indicating that higher BMI is an independent risk factor for BPH (27)(28)(29). Meanwhile, OS levels increased when BMI increased (30).…”
Section: Discussionsupporting
confidence: 94%
“…Expensive MRI examination has also not found an increasingly wide utilization in detecting prostate except for patients with suspected prostate cancer. Herein, the criteria for inclusion in this trial are abdominal ultrasound imaging with no suspicion of prostate cancer, and the volume of the prostate is determined by height (cm) × width (cm) × length (cm) × π/6 based on the abdominal ultrasound measurements, the normal volume is 20–30 mL, the secretion of PSA is influenced by prostate volume size, so there is no special requirement for PSA levels ( 22 ). It is noteworthy that the individuals enrolled in the group had undergone health examinations for more than 2 years, which was helpful to exclude inappropriate candidates.…”
Section: Methodsmentioning
confidence: 99%